The biological method of increasing the fertility of soils (Experimental biology, 2016)
At the present time, in Kazakhstan there is an environmental problem - salinization of soils. One way to restore the fertility of saline soils is the development and application of biomeliorants based on plant waste. Application biomeliorants improves soil structure, reduces salinity and activates the microbial soil processes. The new biological method to increase the fertility of second-saline soils by applying new biomeliorant obtained by cellulolytic bacteria was developed. Application of the method leads to the activation of soil microbial processes, creates conditions for the transit of salt removal of soluble compounds, toxic effects on the development of rice plants, and normalizes the pH of saline soil, which contributes to a substantial desalination of the soil, improving its fertility and creates favorable conditions for the development of plants. This rice yield increased by 1.7 times compared to the control.
Keywords: soil; secondary salinization; cellulolytic bacteria; solid-state fermentation; waste rice.